Ligand relay catalysis for cobalt-catalyzed sequential hydrosilylation and hydrohydrazidation of terminal alkynes - Yufeng Sun; Jun Guo; Xuzhong Shen; Zhan Lu (Nature Communications, 2022)
In organic chemistry, performing sequential catalytic cycles with a single catalyst improves efficiency. Here the authors present a methodology to functionalize alkynes with nitrogen and silicon atoms, through two catalytic cycles with a homogeneous cobalt catalyst, which is bound to different ligands in each cycle.